Serological investigation of in Korean preterm infants - Ho Seon Eun; Soon Min Lee; Min Soo Park; Kook In Park; Ran Namgung; Chul Lee (Korean Pediatric Society, 2013)
PurposeUreaplasma colonization is related with perinatal complications in preterm infants. Little is known about the difference in virulence among various Ureaplasma urealyticum serovars. The aim of this study was to determine U. urealyticum serovars of preterm infants in order to assess whether any of the serovars were associated with bronchopulmonary dysplasia (BPD).MethodsThree hundred forty-four preterm infants with a gestational age less than 34 weeks admitted to Gangnam Severance Hospital neonatal intensive care unit from July 2011 to December 2012 were included in this study. Tracheal and gastric aspirations were conducted on infants to confirm Ureaplasma colonization. Ureaplasma colonization was confirmed in 9% of infants, of these, serovars were determined by real-time polymerase chain reaction.ResultsA total of 31 infants (gestational age, 29.3±3.1 weeks; birth weight, 1,170±790 g) were U. urealyticum positive. The Ureaplasma positive group treated for more days with oxygen and ventilation than the negative group (P<0.05). Histologic chorioamnionitis and moderate to severe BPD were more frequent in the Ureaplasma positive group than in the negative group (P<0.05). U. urealyticum isolates were either found to be a mixture of multiple serovars (32%), serovar 9 alone or combined with other serovars (39%), serovar 11 (26%), 2 (13%), 8 (10%), 10 (13%), and 13 (25%). No individual serovars were significantly associated with moderate to severe BPD and chorioamnionitis.ConclusionThis is the first study to describe the distribution of U. urealyticum serovars from Korean preterm infants. Ureaplasma-colonized infants showed higher incidence of BPD and chorioamnionitis.